Scaling out agroecology from the school garden: the importance of culture, food, and place. Issue 7 (14th September 2019) - Ferguson, Bruce G.; Morales, Helda; Chung, Kimberly; Nigh, Ron
ABSTRACT: We explore potential and limitations for agroecological scaling through formal education, using the LabVida school gardens program in Chiapas, Mexico as a case study. Through LabVida training, educators gained an appreciation of agroecology and learned to apply agroecological practices, although their understanding of agroecological principles and scientific process remained limited. The greatest program impact was on educators' eating habits, and their perception of the value of local knowledge and its relevance to school work. The case study demonstrates the potential of garden and food-system work to leverage institutional resources in ways that can improve educational outcomes, including agroecological literacy. Increased awareness of agroecology and the value of local knowledge may intersect with other drivers of scaling, including markets, organizational fabric, and policy.